Assessment of the effect of anthropometric data on the alterations of cardiovascular parameters in Lithuanian elite male basketball players during physical load - Zumbakyte-Sermuksniene, R.; Kajeniene, A.; Berskiene, K.; Daunoraviciene, A.; Sedereviciute-Kandrataviciene, R. (Medicina, 2012)
Objectives. The aim of the study was to assess the effect of the anthropometric data of basketball players on the alterations of cardiovascular parameters during the physical load applying the model of integrated evaluation.